2023
DOI: 10.3390/ijerph20032225
|View full text |Cite
|
Sign up to set email alerts
|

Sentiment Analysis on Twitter: Role of Healthcare Professionals in the Global Conversation during the AstraZeneca Vaccine Suspension

Abstract: The vaccines against COVID-19 arrived in Spain at the end of 2020 along with vaccination campaigns which were not free of controversy. The debate was fueled by the adverse effects following the administration of the AstraZeneca-Oxford (AZ) vaccine in some European countries, eventually leading to its temporary suspension as a precautionary measure. In the present study, we analyze the healthcare professionals’ conversations, sentiment, polarity, and intensity on social media during two periods in 2021: the one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…An emotion analysis revealed that trust was the most predominant emotion, followed by anticipation, fear, and sadness [ 37 ]. Ruiz-Núñez examined the tweets of healthcare providers in Spain at two different time periods (one closest to the 2021 suspension of the AstraZeneca vaccine and the other 30 days later), reporting that negative tweets sent by healthcare providers against the corona vaccine had an impact on the prevention of COVID-19 [ 38 ]. Ong et al investigated tweets from Malaysian Twitter ® users related to additional doses of vaccines and found that they were interested in the type of vaccine, the effect of the vaccine, and the vaccination schedule [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…An emotion analysis revealed that trust was the most predominant emotion, followed by anticipation, fear, and sadness [ 37 ]. Ruiz-Núñez examined the tweets of healthcare providers in Spain at two different time periods (one closest to the 2021 suspension of the AstraZeneca vaccine and the other 30 days later), reporting that negative tweets sent by healthcare providers against the corona vaccine had an impact on the prevention of COVID-19 [ 38 ]. Ong et al investigated tweets from Malaysian Twitter ® users related to additional doses of vaccines and found that they were interested in the type of vaccine, the effect of the vaccine, and the vaccination schedule [ 39 ].…”
Section: Discussionmentioning
confidence: 99%